Penyuluhan Terkait Pentingnya Komunikasi Branding dan Strategi Promosi Untuk Meningkatkan Pelanggan Usaha Mikro Kecil Menengah - Andrianto Prasetya Nugroho; Zulfa Zakiatul Hidayah; Erin Soleha; Suhendra Suhendra; Rizka Estisia Pratiwi (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
With the advancement of technology, competition in the mid-to-low-end business sector has intensified. Both large businesses and Micro, Small and Medium Enterprises (MSMEs) are facing challenges and obstacles. On the other hand, MSMEs will have greater opportunities to market their products due to advances in information technology. When starting a business, branding communication is very important. Each individual has a different brand image. By using the right promotional strategy, effective branding communication can provide consumers with the opportunity to recognize certain goods and services, evaluate their quality, reduce purchase risks, and get different experiences and satisfaction. Every business field must have a strategy to increase sales. The right promotional strategy can communicate branding well. To achieve goals, every business sector needs a promotional strategy, especially for micro, small and medium enterprises (MSMEs). Promotion planning is carried out to improve services and sales by introducing products to potential customers and improving services by focusing on online-based promotions by utilizing social media and marketing through the marketplace. In a startup business, where the business has just started and continues to grow, business actors are considered necessary to continue to develop products and find the right target market. The purpose of this Community Service activity is to provide an assessment of branding and promotional communication strategies to increase customers for this startup business.